Beyond weight loss: digital therapeutic for behavioral change and psychological well-being for individuals with overweight and obesity in a primary healthcare setting—A randomized controlled pilot study - Aukan, Marthe Isaksen; Larsen, Maria Arlèn; Melan, Tone Iren; Salvesen, Øyvind Olav (Frontiers in Digital Health, 2025)
ObjectiveMobile health (mHealth) through digital therapeutics (DTx) offer a promising approach to obesity management. This study evaluated the effectiveness of the Lifeness DTx for obesity care and its effect on anthropometrics, reward-related eating behaviors and quality of life in individuals with overweight and obesity within a community-based healthcare setting.MethodsA 12-week randomized controlled trial was conducted. Adults (BMI ≥ 27 kg/m2, and central obesity) were recruited from municipal Healthy Life Centers in Norway. The intervention group (IG) received standard care plus full DTx app with program functionality and digital follow-up, whereas the control group (CG) received standard care with limited app functions and no DTx program. Outcome variables were measured at baseline and after 12 weeks.ResultsNo significant changes in body weight, or differences between groups were observed at W12. The IG showed reductions in waist circumference (−3.4 cm, p = 0.008, d = −0.926), waist-to-height ratio (−0.02, p = 0.008, d = −0.929), improvements on hedonic eating behavior, indicated by reduced disinhibition (−1.6, p = 0.013, d = −0.907), as well as increased quality of life (+5.0, p = 0.019, d = 0.899). Both groups increased self-esteem (IG +9.8, p = 0.018, d = 0.911, and CG +12, p = 0.050, d = 0.838).ConclusionThe DTx intervention was associated with improvements in central adiposity, reward-related eating behaviors, and psychological well-being beyond weight loss. These findings provide preliminary evidence that digital therapeutics may represent a feasible and scalable approach to support personalized obesity care in primary healthcare settings. Larger, adequately powered trials are needed to confirm these results.Clinical Trial Registrationclinicaltrials.gov, identifier NCT06667843 (Initial Release: 10/15/2024).